Influential or Influenced: Exploring Factors Affecting Academic Success of Tadris Biology Students in Islamic Higher Education - Fitria, Kelsi Okta; Sastria, Emayulia; Damni, Albertos (Magister Pendidikan Biologi, Universitas Negeri Medan, 2023)
Islamic Higher Education often serves as a pivotal educational centre, cultivating knowledge and fostering academic growth. Understanding the factors influencing students' academic performance, particularly in specialized fields like Tadris Biology, holds significance in optimising educational strategies and support systems. This study aims to ascertain the variables that impact the Cumulative Achievement Index of Tadris Biology students at Islamic universities. The research methodology employed is qualitative, using Grounded Theory analysis techniques. Data was collected by administering a questionnaire and conducting in-depth interviews with 67 students. The findings indicate that prior educational experience, gender, and parental income affect GPA. Students with a scientific background, female students, and those from higher-income households tend to achieve higher GPAs. Conversely, social media usage can hurt academic performance, while involvement in extracurricular activities has no discernible effect. The benefit of this research is that it explores factors affecting the academic success of tardis biology students in Islamic higher education. This research holds inherent value in unravelling the nuanced aspects that shape the academic success of Tadris Biology students within the realm of Islamic higher education. Understanding these dynamics can pave the way for tailored interventions and support systems to enhance student outcomes in this specialised field.